Correlation of the Osteoarthritis Susceptibility Variants That Map to Chromosome 20q13 With an Expression Quantitative Trait Locus Operating on NCOA3 and With Functional Variation at the Polymorphism rs116855380. Issue 11 (November 2015) - Gee, Fiona; Rushton, Michael D.; Loughlin, John; Reynard, Louise N.
Abstract : Objective: To functionally characterize the osteoarthritis (OA) susceptibility variants that map to a region of high linkage disequilibrium (LD) on chromosome 20q13 marked by the single‐nucleotide polymorphism (SNP) rs6094710 and encompassing NCOA3 and SULF2 . Methods: Nucleic acids were extracted from the cartilage of OA patients. Overall and allelic expression of NCOA3 and SULF2 were measured by quantitative reverse transcription–polymerase chain reaction and pyrosequencing, respectively. The functional effect of SNPs within the 20q13 locus was assessed in vitro using luciferase reporter constructs and electrophoretic mobility shift assays (EMSAs). The in vivo effect of nuclear receptor coactivator 3 (NCOA3) protein depletion on primary human OA articular cartilage chondrocytes was assessed using RNA interference. Results: Expression of NCOA3 correlated with the genotype at rs6094710 ( P  = 0.006), and the gene demonstrated allelic expression imbalance (AEI) in individuals heterozygous for the SNP (mean AEI 1.21; P < 0.0001). In both instances, expression of the OA‐associated allele was reduced. In addition, there was reduced enhancer activity of the OA‐associated allele of rs116855380, a SNP in perfect LD with rs6094710 in luciferase assays ( P < 0.001). EMSAs demonstrated a protein complex binding with reduced affinity to this allele. Depletion of NCOA3 led to significant changes (all P < 0.05) in the expression of genes involved in cartilage homeostasis. Conclusion: NCOA3 is subject to a cis ‐acting expression quantitative trait locus in articular cartilage, which correlates with the OA association signal and with the OA‐associated allele of the functional SNP rs116855380, a SNP that is located only 10.3 kb upstream of NCOA3 . These findings elucidate the effect of the association of the 20q13 region on OA cartilage and provide compelling evidence of a potentially causal candidate SNP.